Understanding research, science, and technology parks : global best practices, report of a symposium - Wessner, Charles W. (National Academies Press, 2009)
"Many nations are currently adopting a variety of directed strategies to launch and support research parks, often with significant financial commitments and policy support. By better understanding how research parks of other nations operate, we can seek to improve the scale and contributions of parks in the U.S. To that end, the National Academies convened an international conference on global best practices in research parks. This volume, a report of the conference, includes discussion of the diverse roles that research parks in both universities and laboratories play in national innovation systems. The presentations identify common challenges and demonstrate substantial differences in research park programs around the world"--Publisher's website